ISOLASI KALSIUM OKSIDA (CAO) PADA CANGKANG SOTONG (CUTTLEFISH) DENGAN PROSES KALSINASI MENGGUNAKAN ASAM NITRAT DALAM PEMBUATAN PRECIPITATED CALSIUM CARBONAT (PCC) - Meilianti, Meilianti (Universitas Muhammadiyah Palembang, 2017)
Cuttlefish also called cuttlefish bone is internal skin utilized a cuttlefish. Cuttlefish shells in the form of solid wastes that are not mature and have not been optimally. Solid waste in the form of shells only used as a bird feed and tortoise because they contain calcium car bonate, sodium chloride, calcium phosphate, and magnecium salt with calcium contents calcium carbonate around 85% calcium powder to obtain levels of field, such as health, food, and for high carbonate (CaO) recovery processes and determining the best temp erature of the calcined shell to produce precipitated calcium carbonate (PCC). In the process of dry sciling (powder) process at a temperature of 800oC, 850oC, 900oC, 950oC, and 1000oC specified 30 minuted and 90 minutes after obtaining CaO content by titration method, the addition of nitric acid (HNO3) with concentration variation 1,5 M, 1,75 M, 2,00 M, 2,25 M, and 2,5 M. After determining the levels of CaCO3 by titration method, after passing through several stages of the process, the analysis of CaCO3 content and calculation with the formula obtained that the level of calcium carbonate in the form of PCC with 99.7% purity with the concentration of HNO3, 2.5 M and calcination 1000oC.